Design of two bearings with sealing system for the top roll shaft of sugar cane mill - Mora Perdomo, Walter; Rivas Murillo, John Sandro; Coronado Marín, John Jairo (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
The bronze bearings currently used in sugar cane mills undergo an excessive wear due to both, the extraneous matter entering in the bearing gap when the shaft lift by effect of cane passing through the mill and heating caused by failures in both the lubrication and the refrigeration systems. In order to solve this problems two bearing were designed: one cooled in the box and other cooled in the roofing tile, both using a sealing system. Finite Elements Analysis of the designs showed that they will have a good mechanical and thermal performance